A study on the thermal (heat conductivity and resistivity), acoustical (sound absoprtion and tranmission), and fire resistivity properties of sugarcane (saccharum officianarum) bagasse (scb) drywall panels - Brillante, Julius Benedict A. (2018)
The growing amounts of agricultural wastes in the country has led to the development of different methods to optimize the use of the trash produced from agricultural processes. In the advent of building sustainability and green architecture, the idea of integrating these wastes into building materials has been a solution to minimize the improve the performance of buildings and at the same time reduce the amount of agricultural wastes thrown away by farms and plants.This undergraduate thesis entitled ""A Study on the Thermal (Heat Conductivity and Resistivity), Acoustical (Sound absorption and Transmission), and Fire Resistivity Properties of SCB Drywall Panels"", aimed to produce a building material, addressing the issues on agricultural waste optimization and building material sustainability. Throughout this research, the properties thermal, acoustical and fire resistivity of the developed material were thoroughly explored.The Lee's Disc Apparatus, a reverberation chamber and diffuse sound field transmission model, and point flame test were used to determine the thermal, acoustical and fire resistivity properties of SCB Drywall Panels, respectively.Results showed that among formulations, SCB Drywall Panels formulation C-25% SCB, 15% perlite powder, and 60% gypsum-exhibits the most thermal resistive (0.84 ft2hF/Btu) and least thermal conductive (0.08 W/m-K). The same formulation of SCB Drywall panel has an NRC rating of 0.25 (hardly absorbing) and an STC rating of 34 (fair). Finally, all formulations were one hour fire resistive, conforming to the standards set by the National Building Code of the Philippines (NBCP). With these, SCB Drywall Panels are suitable for drywall partitions and ceiling applications in spaces requiring ample amount of sound insulation, thermal comfort, and fire resistivity.This research study is an exploration study that aimed to provide baseline information concerning the use of SCB in the development of Drywall Panels. Testing for other qualities not mentioned above and the effects of the variety of the sugarcane used to the properties of the developed material are beyond the scope of this study.